1996
DOI: 10.1152/jappl.1996.81.2.943
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-derived nitric oxide activity in forearm vessels of tennis players

Abstract: The aim of this study was to determine whether physical conditioning induced by a repetitive exercise stimulus would elicit changes in the response of forearm resistance vessels to an infusion of substances that modulate nitric oxide synthesis. Forearm blood flow responses to a 5-min ischemic stimulus and intrabrachial infusion of acetylcholine, sodium nitroprusside, and NG-monomethyl-L-arginine were examined in the preferred and nonpreferred limbs of eight habitual tennis players. Forearm volume, girth, and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 0 publications
5
76
0
Order By: Relevance
“…The vasodilator response of the diabetic patients to ACh was depressed relative to that of normal subjects recruited in a recent study (20). These normal subjects were younger than the diabetic subjects, their ages averaging 28 and 43 yr, respectively.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The vasodilator response of the diabetic patients to ACh was depressed relative to that of normal subjects recruited in a recent study (20). These normal subjects were younger than the diabetic subjects, their ages averaging 28 and 43 yr, respectively.…”
Section: Discussionmentioning
confidence: 68%
“…In addition to studying the effects of ACE inhibition in the diabetic patients, their pretreatment results were compared with those of eight healthy male volunteers (28 Ϯ 2 yr) previously studied (20) and who had attended the laboratory on one occasion when forearm vascular responses to intrabrachial ACh and SNP infusion were determined. This was also undertaken during the initial session attended by the diabetic patients.…”
Section: Methodsmentioning
confidence: 99%
“…Green et al 37 reported that exercise training enhanced reactive hyperemic response, as an index of vascular structure, in the preferred arm but not in nonpreferred arm without influencing basal or ACh-induced vasodilation in tennis players. Although the discrepancy in the results of the present study may be attributable to the different stimulus, aerobic exercise and IPC, we cannot deny the possibility that repletion of IPC stimulus alters vascular structure per se.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that changes in endothelial function represent short-term adaptations to training and are eventually replaced by structural or other adaptations (Green et al 2004a). This is illustrated by the observation that the endothelial function in forearm vessels of long-term tennis players was similar in the dominant and non-dominant arm (Green et al 1996). One should take notice that these subjects played tennis for 13 h per week and that this may have resulted in concomitant training of the non-dominant arm.…”
Section: Discussionmentioning
confidence: 99%